2016
DOI: 10.1261/rna.056531.116
|View full text |Cite
|
Sign up to set email alerts
|

tRNA base methylation identification and quantification via high-throughput sequencing

Abstract: Eukaryotic transfer RNAs contain on average 14 modifications. Investigations of their biological functions require the determination of the modification sites and the dynamic variations of the modification fraction. Base methylation represents a major class of tRNA modification. Although many approaches have been used to identify tRNA base methylations, including sequencing, they are generally qualitative and do not report the information on the modification fraction. Dynamic mRNA modifications have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
237
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(263 citation statements)
references
References 48 publications
26
237
0
Order By: Relevance
“…Our results confirmed that m 1 A58 is globally present in the cytosolic tRNAs (Figure 1C and S2F). A recent study reported m 1 A at position 9 in cytosolic tRNA Asp(GUC) (Clark et al, 2016); this site is also detected by m 1 A-MAP (Figure 1D). Collectively, these observations suggest that m 1 A-MAP is highly sensitive in detecting m 1 A at single-base resolution.…”
Section: Resultsmentioning
confidence: 54%
“…Our results confirmed that m 1 A58 is globally present in the cytosolic tRNAs (Figure 1C and S2F). A recent study reported m 1 A at position 9 in cytosolic tRNA Asp(GUC) (Clark et al, 2016); this site is also detected by m 1 A-MAP (Figure 1D). Collectively, these observations suggest that m 1 A-MAP is highly sensitive in detecting m 1 A at single-base resolution.…”
Section: Resultsmentioning
confidence: 54%
“…As a result, group II intron RTs have higher fidelity, processivity and strand displacement activity than retroviral RTs, along with a highly proficient end-to-end template switching activity that is minimally dependent upon base pairing (Mohr et al, 2013). Recently, new methods for producing group II intron RTs in soluble form with high yield and activity have enabled their use for biotechnological applications, including new approaches for next-generation RNA sequencing (RNA-seq), identification of RNA post-transcriptional modifications, and RNA structure mapping (Clark et al, 2016; Nottingham et al, 2016; Zheng et al, 2015; Zubradt et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This method holds substantial promise for the comprehensive characterization of transcriptome-wide RNA methylation patterns. Similarly, ARM-seq (AlkB-facilitated RNA methylation sequencing) or DM-tRNA-seq (demethylase tRNA sequencing) revealed a complex modification landscape of full-length tRNAs and tRNA fragments [3032]. …”
Section: Introductionmentioning
confidence: 99%